Labor da carne: o trabalho em um frigorífico de aves - Amanda Aparecida Marcatti (2014)
The objective of this study is describe and analyze the work as well as their conditions of realization in a poultry slaughtering. In recent years some studies that addressed the work in poultry slaughtering especially in the southern region of the country, atented specifically at the worker's health, showed us that was necessary to examine in a wide way the work and also Agroindustrial Chain for Beef Production in Brazil. With this aim, in this study was used as a methodology semi-structured interviews with employees of the poultry slaughtering: totaly ten workers who were allocated in different sectors of the production line were interviewed. This dissertation consists of four chapters. In the first chapter we sought to introduce the reader to the topic researched, as well as reporte the process to this research. The second chapter has focused on the macro analysis of Agroindustrial Chain for Beef Production in Brazil, reflecting about the production of the meat as a constitutive part of Agribusiness commodity production. In this chapter we also characterize the work in the Brazilian's slaughterhouses. The third chapter deals with the analysis of the work in the capitalist system of production, as well as their ways of management and production control. In this we characterize the work in the pultry slaugtering in general under the optical of Taylorism and Fordism production. The results of such research are presented in the fourth chapter of the dissertation, in it we analyse the subjects and the learning processes at work, also the conditions, rythim (pace) and intensity of production in the poultry slaughtering, as well as we describe the production according to the account of respondents. The results of the researcher indicate that the work in poultry slaughtering is marked by the degradation of physical and metal workers's health, who perform it on extensive journeys of daily work, strong pressure and management control, cadenced by the rhythm of the machines.